Joint Watermarking and Encryption of Color Images in the Fibonacci-Haar Domain. (14th September 2009) - Battisti, Federica; Cancellaro, Michela; Boato, Giulia; Carli, Marco; Neri, Alessandro
Abstract : A novel method for watermarking and ciphering color images, based on the joint use of a key-dependent wavelet transform with a secure cryptographic scheme, is presented. The system allows to watermark encrypted data without requiring the knowledge of the original data and also to cipher watermarked data without damaging the embedded signal. Since different areas of the proposed transform domain are used for encryption and watermarking, the extraction of the hidden information can be performed without deciphering the cover data and it is also possible to decipher watermarked data without removing the watermark. Experimental results show the effectiveness of the proposed scheme.